Silicon Protection of Sugar Beet (Beta vulgaris) Against Field Dodder (Cuscuta campestris): Preliminary Analysis - Aliverdi, Akbar; Mansouri, Hamed (Plant-environment interactions (Hoboken, N.J. : 2018), 2025)
ABSTRACT This preliminary study aimed to investigate the mitigation effect of silicon (Si) on field dodder‐induced stress in sugar beet. The experiment was conducted as a completely randomized design with three factors, including parasitic infection (non‐parasitized and dodder‐parasitized sugar beet), Si source (5 mM Si in the form of Na2SiO3 or K2SiO3), and Si application method (control, seed pretreatment, irrigation, and foliar spraying). Without Si, field dodder caused a 44.9% reduction in shoot biomass and a 57.5% reduction in root biomass. Although pretreating seeds with Si solutions accelerated emergence, it did not significantly influence any other traits measured in the sugar beet. Sugar beets that received Si through irrigation exhibited better protection against field dodder than those that were sprayed; furthermore, K2SiO3 proved to be more effective than Na2SiO3. Irrigating or spraying sugar beet with K2SiO3 reduced field dodder biomass by 60%–65%, while the reduction ranged from 20% to 35% with Na2SiO3. The highest lignin content was observed by watering and spraying dodder‐parasitized sugar beet with K2SiO3, resulting in a 4.2‐fold increase through watering and a 3.8‐fold increase through spraying. Field dodder infection led to increased activity of enzymes involved in scavenging reactive oxygen species, including catalase, guaiacol peroxidase, superoxide dismutase, and lipoxygenase in sugar beet. The application of Si further increased the activities of superoxide dismutase and lipoxygenase. This preliminary study suggests that irrigating with K2SiO3 can help reduce damage caused by field dodder in sugar beet. However, additional research is necessary to evaluate the crop's response at the field level.